FRI0047 The Patient Perspective on Absence of Disease Activity in Rheumatoid Arthritis: A Survey to Identify Key Domains of Patient Perceived Remission. (9th June 2015) - van Tuyl, L.H.; Sadlonova, M.; Hewlett, S.; Davis, B.; Flurey, C.; Goel, N.; Gossec, L.; Heegaard Brahe, C.; Hill, C.; Hoogland, W.; Kirwan, J.; L Hetland, M.; et al.
Abstract : Background: Guidelines suggest treatment in rheumatoid arthritis (RA) should be targeted at remission, in close consultation with the patient. Our recent qualitative study of the patient perspective on remission in RA identified reduction or absence of a) certain symptoms and b) impact of the disease on daily life, as well as c) a return to normal life as important themes. Objectives: The current study aimed to determine the relative importance of the many aspects of remission identified within these three themes to produce a short list of the most important aspects to inform future research. Methods: RA patients from the Netherlands, the United Kingdom (UK), Austria, Denmark, France, and the United States (US) were asked to complete a survey that contained all 26 domains of remission identified in our qualitative study. Patients were asked to rate domains for importance ("not important", "important", or "essential" to characterise a period of remission) and if important or essential, whether this domain needs to be `'less", 'almost gone', or 'gone' to reflect remission. In addition, respondents were asked to determine their personal top 3 of most important/essential domains that characterise remission. First, frequency of a particular domain mentioned in the top 3 was calculated. Second, domains that >30% of patients identified as "not important" were removed. The remaining domains were sorted on the percentage of patients that evaluated a particular domain as "essential". Results: Data from 274 RA patients were collected (54 Netherlands, 33 UK, 51 Austria, 43 Denmark, 43 France, and 50 US), including 75% females, mean (SD) age 57 (13) years, disease duration 12 (9) years (range 0 to 50). 38% reported they were currently in remission and 41% reported erosive disease. The most often mentioned domains in the top 3 were: pain (n=188, 67%), fatigue (n=91, 33%) and independence (n=53, 19%). Domains that were most frequently rated as "essential" to characterise a period of remission were: pain (n=163, 60%), being mobile (n=142, 52%), physical function (n=140, 51%), being independent (n=129, 47%) and fatigue (n=113, 41%). Pain needed to be less (13%), almost gone (42%) or gone (45%) to reflect remission. Similar patterns were seen for fatigue (23%, 40%, 37%), independence (16%, 31%, 53%), mobility (16%, 35%, 49%) and physical functioning (14%, 29%, 57%). Conclusions: The most important domains of RA disease activity that need to be improved in order to reflect remission from a patient perspective are pain, fatigue, independence, mobility and physical functioning. Measurement of these domains in low disease activity will be a next challenge. Disclosure of Interest: None declared